IMPLEMENTATION OF FINITE STATE AUTOMATA ON THE DATE TO SEASON CONVERSION ENGINE BASED ON PRANATA MANGSA SEASON CALENDAR - iboy, rahmat satria buana; Gata, Windu; Bayhaqy, Achmad; Sulaeman, Okky Robiana; Merlina, Nita (Jurnal Sistem Informasi dan Ilmu Komputer, 2022)
The world is now starting the trend of going green or back to nature. The slogan goes green or back to nature can also be interpreted as living in harmony with nature. Our beloved country of Indonesia has implemented a harmonious life with nature, we can find it in the Javanese planting season calendar called Pranata Mangsa. In the pranata mangsa, we are taught the method of living in harmony, especially in an agricultural system. Harmony with nature means harmony between seasons, weather, living things, and types of plants. If everything is applied, there will be harmonization between all elements both from outside and inside so that additional elements such as chemical fertilizers and pesticides in agriculture, which essentially eliminate the harmonization of nature itself, are not needed. The implementation of Finite State Automata on the farming season calendar is expected to be able to educate and make it easier for farmers in particular and the Indonesian people, in general, to able to recognize the farming time and apply it to daily life. The final result of this research is the calendar system that can convert the date and month in the masehi calendar into the period or season of the pranata mangsa system. Key word : FSA, DFA, calendar, pranata mangsa, season